APLIKASI TES BAKAT MINAT BERBASIS KOMPUTER UNTUK PEMETAAN PILIHAN JURUSAN SISWA SMK DENGAN MENGGUNAKAN DAT DAN RMIB - Ernawati, Sri; Anwariningsih, Sri Huning (TALENTA, 2014)
Education is a process of individual potential development into competence. Their competence reflect an individual ability and skill in doing the task or job. Each individual has many important characteristics which talent and interest is one of them. Interest is an develoment process in mixing all of existing capabilities to mobilize individuals at an activity that is interested tothem. Meanwhile, talent is a characteristicscombination of individual capacity to acquire some special knowledge, skills and organized response. Characteristics talents and interests need to be understood by students and teachers. If someone studies or works in areas of their interest and is supported with appropriate talent so it will give the spirit in studying or living. Talent can be seen with Differential Aptitude Test (DAT) assay, and interest can be seen with the Rothwell Miller The objective of this study is (1) Establishment of a talet and interest test application computers based that can assist for SMK students, (2) Description of the acceptance and satisfaction level of students and teachers toward the talent and interest test application based on computers thatcan assist in track attraction. This study is designed with two phase: (1) Phase I is to development a computerbased application of talent and interest test with the Research and Development, and (2) Phase II is to test the level of acceptance and satisfaction from user toward this talent and interest test application using modelsTechnology Acceptance Model (TAM). Based on the results of TAM analysis, it can be concluded that students find an easy to use the existing application of talent and interest test so that the level of satisfaction and acceptance was achieved. The obtaining of effective contribution is 11.7%.